2013
DOI: 10.1007/s10919-013-0155-z
|View full text |Cite
|
Sign up to set email alerts
|

Eye Contact Evokes Blushing Independently of Negative Affect

Abstract: To determine whether eye contact elicits blushing due to anxiety, forehead blood flow was measured during a stressful quiz and self-disclosure. The investigator maintained eye contact with 19 participants whereas, in another 40 cases, the investigator and/or participant wore sunglasses or the investigator left the room (the control group). Anxiety, embarrassment and forehead blood flow increased in both groups during the quiz, consistent with anxiety-evoked blushing. However, during self-disclosure, increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…While there are a handful studies that lend insight into the independent and joint contributions of various nonverbal channels during FtF interactions, the majority of these studies were either conducted with static images 12 , 13 or posed expressions 14 16 , rather than FtF interactions. In addition, the limited number of studies that did study the impact of different nonverbal cues in FtF dyadic contexts asked participants to wear sunglasses 17 , 18 or covered parts of their bodies 19 , 20 , which inevitably alters the appearance of the target individual and reduces both the ecological validity and generalizability of results. By using identical avatars across conditions and only allowing the nonverbal information to differ, the present study offers an ideal balance between experimental control and ecological validity 3 .…”
Section: Introductionmentioning
confidence: 99%
“…While there are a handful studies that lend insight into the independent and joint contributions of various nonverbal channels during FtF interactions, the majority of these studies were either conducted with static images 12 , 13 or posed expressions 14 16 , rather than FtF interactions. In addition, the limited number of studies that did study the impact of different nonverbal cues in FtF dyadic contexts asked participants to wear sunglasses 17 , 18 or covered parts of their bodies 19 , 20 , which inevitably alters the appearance of the target individual and reduces both the ecological validity and generalizability of results. By using identical avatars across conditions and only allowing the nonverbal information to differ, the present study offers an ideal balance between experimental control and ecological validity 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used parametric tests, such as analysis of variance (ANOVA) and Pearson's correlation test, to analyse the SkBF and heart rate (Drummond and Su, 2012;Drummond and Bailey, 2013;…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used parametric tests, such as analysis of variance (ANOVA) and Pearson’s correlation test, to analyse the SkBF and heart rate ( Drummond and Su, 2012 ; Drummond and Bailey, 2013 ; Kashima et al, 2013 ). We used two-way repeated measures ANOVA to examine the effect of blushing and facial expressions on physiological and subjective indices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of biased appraisal of interoceptive information which leads to overestimation of physiological change in socially anxious people is supported by a number of studies that have found that socially anxious individuals who are informed that their physiological anxiety level (e.g., heart rate) is increasing during a social situation (regardless of the veracity of this information) report greater subjective anxiety than if they are told their symptoms are diminishing (Wells & Papageorgiou, 2001). Studies with false feedback of blushing confirmed that false positive feedback increased embarrassment and subjective feelings of blushing, whereas physiological blushing was less affected by the false feedback (Dijk et al, 2009;Drummond et al, 2003). These results support the idea that the perception or interpretation of physiological functioning, rather than actual physiological functioning, is included in the creation of internal representations of socially anxious individuals.…”
Section: The Relationship Between Blushing and Social Anxietymentioning
confidence: 93%